The Development of A Magnetic Classroom Agreement Board (Pakeman) as Learning Media to Foster Discipline in Children Aged 5–6 Years - Euis Saripah; Hamid Patilima; Sisca Cletus Lamatokan (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Discipline learning in early childhood education institutions still faces several challenges, including overly instructive approaches, less engaging learning media, and limited child participation in establishing classroom rules. This study aimed to develop a magnetic-based classroom agreement board as an effective learning medium to foster positive discipline among young children through a participatory approach. This research employed the ADDIE development model, adapted into five stages. The research subjects were 15 children in Group B (aged 5–6 years) at TK Negeri Manonjaya, Tasikmalaya. Data were collected through interviews, observations, questionnaires, and expert validation, and were analyzed using qualitative and quantitative approaches. The resulting product was a magnetic classroom agreement board consisting of a magnetic board as the main surface for attaching agreement cards, 15 circular agreement cards with concrete illustrations, and supporting materials including a header poster, guidebook, tutorial video, and blank templates. Theoretical validation indicated a “Very Feasible” category (92%), while empirical validation reached 93.3%. The effectiveness test showed a 61.7% improvement in children’s disciplinary behavior with an improvement score of 0.50 (effective category), accompanied by positive developmental shifts across all participants. These findings indicate that participatory-based media can serve as an effective, practical, and sustainable tool for fostering positive discipline in early childhood education.